Answer:
Step-by-step explanation:
Compound inequality has been given as,
12(2x - 10) + 24 ≥ 48 Or 6x + 15 - 9x ≥ 6
By simplifying it further,
12(2x - 10) + 24 ≥ 48
![\frac{12(2x - 10)}{12}+\frac{24}{12}\geq \frac{48}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B12%282x%20-%2010%29%7D%7B12%7D%2B%5Cfrac%7B24%7D%7B12%7D%5Cgeq%20%5Cfrac%7B48%7D%7B12%7D)
(2x - 10) + 2 ≥ 4
(2x - 10) + 2 - 2 ≥ 4 - 2
2x - 10 ≥ 2
2x - 10 + 10 ≥ 2 + 10
2x ≥ 12
![\frac{2x}{2}\geq \frac{12}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B2x%7D%7B2%7D%5Cgeq%20%5Cfrac%7B12%7D%7B2%7D)
x ≥ 6
6x + 15 - 9x ≥ 6
(6x - 9x) + 15 ≥ 6
(-3x) + 15 ≥ 6
-3x + 15 - 15 ≥ 6 - 15
-3x ≥ -9
3x ≤ 9
x ≤ 3
We have to plot the inequality on a number line
x ≥ 6 Or x ≤ 3
First make sure that one of the variable has the same coefficient in each equations.
For example lets use:
y=x+3
2y=3x-1
Since neither the y's or x's are the same, we must multiply the equations to make them the same. I am going to multiply the first equation by 2 so I can eliminate the y's.
So we get:
2y=2x+3
2y=3x-1
Then we subtract the second equation from the first to eliminate the y's. So we end up with 0=-x+4 and now we solve for x
0=-x+4
x=4
Now we plug in our x into either original to get the y-value. I am using the first
y=x+3
y=4+3
So the x=4 and y=7
Hope this helps!
Answer:
The annual growth rate between 1985 and 2005 is 0.95%
The value of the house in the year 2010 is $152,018
Step-by-step explanation:
Let the annual growth rate = r
Value of the house in year 1985 = $120,000
Value of the house in year 2005 = $145,000
Time (t) = 2005 - 1985
= 20 years
A = P (1 + r)^t
145000 = 120000 (1 + r) ^20
(1 +r)^20 = 145000 / 120000
(1 +r)^20= 1.2083
(1 +r)^20= (1.2083)^1/20
(1 +r)^20= 1.0095
r = 1.0095 - 1
r = 0.0095
r% = 0.0095 x 100
= 0.95%
Value of the house in year 2010
=145000(1 + r)^5
=145000 (1 + 0.0095)^5
= 145000 x 1.0484
=$152,018
Answer:
In the step-by-step explanation!
Step-by-step explanation:
Not sure if it is too late but here:
1.)
![\frac{1}{\alpha}+\frac{1}{\beta} \\\frac{\beta}{\alpha \beta } +\frac{\alpha}{\alpha \beta } \\\frac{\alpha +\beta }{\alpha \beta }](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Calpha%7D%2B%5Cfrac%7B1%7D%7B%5Cbeta%7D%20%5C%5C%5Cfrac%7B%5Cbeta%7D%7B%5Calpha%20%5Cbeta%20%7D%20%2B%5Cfrac%7B%5Calpha%7D%7B%5Calpha%20%5Cbeta%20%7D%20%5C%5C%5Cfrac%7B%5Calpha%20%2B%5Cbeta%20%7D%7B%5Calpha%20%5Cbeta%20%7D)
2.)
![\frac{1 }{\alpha } *\frac{1}{\beta} = \frac{1*1}{\alpha*\beta} =\frac{1}{\alpha \beta}](https://tex.z-dn.net/?f=%5Cfrac%7B1%20%7D%7B%5Calpha%20%7D%20%2A%5Cfrac%7B1%7D%7B%5Cbeta%7D%20%3D%20%5Cfrac%7B1%2A1%7D%7B%5Calpha%2A%5Cbeta%7D%20%3D%5Cfrac%7B1%7D%7B%5Calpha%20%5Cbeta%7D)
3.)
![\frac{1}{\alpha}-\frac{1}{\beta}\\ \frac{\beta}{\alpha \beta } -\frac{\alpha }{\alpha \beta } \\\frac{\beta -\alpha }{\alpha \beta }](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B%5Calpha%7D-%5Cfrac%7B1%7D%7B%5Cbeta%7D%5C%5C%20%5Cfrac%7B%5Cbeta%7D%7B%5Calpha%20%5Cbeta%20%7D%20-%5Cfrac%7B%5Calpha%20%7D%7B%5Calpha%20%5Cbeta%20%7D%20%5C%5C%5Cfrac%7B%5Cbeta%20-%5Calpha%20%7D%7B%5Calpha%20%5Cbeta%20%7D)
Hopes this help! Please give me Brainliest!
Answer:
Step by Step:
x-2y=4
+2y +2y
x=-2y+4
x-2y=4
-4 -4
x-2y-4=0
+2y +2y
x-4=2y
Divid by 2
1/2x-2= y
x=-2y+4
x=-2(1/2x-2)+4
x=-x+4+4
x=-x+8
+x +x
2x= 8
x=4
y=1/2x-2
y=1/2(4)-2
y=2-2
y=0
(4,0)